The Continuous Intention of Online Purchasing in TikTok Shops among FPTP Students - Nur Amira Afiqah Zainal; Anim Zalina Azizan (Research in Management of Technology and Business, 2024)
Information technology has developed very rapidly in this era of globalization, which has led to online shopping experiencing rapid growth in this era. The high statistical rate of online purchase of goods has become a question mark for researchers as to what factors drive customers to buy online. The objective of this study is to identify the influencing factors for the continuous intention to online purchase from TikTok shops among FPTP students and to identify the dominant factor influencing the continuous intention to online purchase from TikTok shops among FPTP students. The scope of this study focuses only on FPTP students at UTHM. To conduct this study, quantitative methods were used to obtain information by distributing an online survey form to 340 respondents. The questionnaire is distributed to respondents through a platform such as Google Forms and sent through social media applications such as WhatsApp, and Telegram. The data obtained will be analyzed using the Statistical Package for Social Science (SPSS) to obtain meaningful results. The results of the study found that among the factors influencing the continuous intention to online purchase from TikTok shops among FPTP students are pricing, quality of information, and shipping. This study found that the pricing factor is the dominant factor that affects the continued intention to make online purchases at TikTok shops. This is because this factor has the highest mean value of 3.976 with a standard deviation of 0.564 which has a high reading level. The limitations faced by researchers are in terms of time constraints and the limited data and information collection process. However, a suggestion that researchers can make in the future is to expand the study population to all university students.